Assertive Behavior Of Bullying Victims At UPTD SMP Negeri 5 Barru - Nurasisa Nurasisa; Taufik Taufik (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2024)
This study focuses on the assertive behavior of students who are victims of bullying, the supporting or inhibiting factors, and the role of guidance and counseling teachers in enhancing students' assertiveness at SMP Negeri 5 Barru. The objectives of this study are to understand the assertive behavior of students who are victims of bullying, to identify the supporting or inhibiting factors of their assertive behavior, and to determine the factors that support or inhibit students' assertive behavior. In UPTD SMP Negeri 5 Barru, this research involves three students, one guidance and counseling teacher, and two research informants. This study adopts a qualitative approach, and data collection methods such as observation, interviews, and documentation are employed. Data analysis involves data reduction, data presentation, and drawing conclusions. Based on the results of the research conducted at the Technical Implementation Unit (UPTD) of SMP Negeri 5 Barru, data were obtained regarding students experiencing issues related to bullying behavior, who were provided with individual and group counseling services. The researcher discussed what bullying is, the impact of bullying on an individual's well-being, and ways to address bullying. The researcher observed changes in student behavior after the implementation of Counseling Guidance Services to Address Bullying Behavior. This indicates that the implementation of Counseling Guidance Services to Address Bullying Behavior among students was successfully carried out through individual and group counseling sessions for three meetings.